Upaya Menumbuhkan Rasa Ingin Tahu Siswa Mengenai Konsep Matematika Menggunakan Abakus - Junaidi Junaidi; Mohammad Rif'at; Bernadeta Ritawati (STKIP Melawi, 2015)
Abstract: This study aimed to grow the students curiosity toward the concept of learning by using media abacus. The problems in this research were the student curiosity in understanding the concept of learning need to be grown, students number counting skill need to be improved, limitations of the learning media owned by the students, the need to foster student understanding toward mathematical concepts, teachers were still rarely use the media in the learning process, difficulty getting instructional media for this so necessary concrete objects as learning media of students. Researcher tried to address these problems by presenting a concrete learning media through the utilization of the natural resources around which